2003
DOI: 10.1002/bip.10512
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human elastin polypeptides self‐assemble into biomaterials with elastin‐like properties

Abstract: Processes involving self-assembly of monomeric units into organized polymeric arrays are currently the subject of much attention, particularly in the areas of nanotechnology and biomaterials. One biological example of a protein polymer with potential for self-organization is elastin. Elastin is the extracellular matrix protein that imparts the properties of extensibility and elastic recoil to large arteries, lung parenchyma, and other tissues. Tropoelastin, the approximately 70 kDa soluble monomeric form of el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
226
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(232 citation statements)
references
References 34 publications
(53 reference statements)
5
226
0
1
Order By: Relevance
“…Elastin is an insoluble, polymeric, ECM protein that provides various tissues in the body with the properties of extensibility and elastic recoil. Elastin is synthesized as tropoelastin (~70kDa), a soluble precursor to insoluble elastin [30]. Tropoelastin has a repeating domain structure, alternating between hydrophobic and crosslinking regions.…”
Section: Biomimetic Mechanical Propertiesmentioning
confidence: 99%
“…Elastin is an insoluble, polymeric, ECM protein that provides various tissues in the body with the properties of extensibility and elastic recoil. Elastin is synthesized as tropoelastin (~70kDa), a soluble precursor to insoluble elastin [30]. Tropoelastin has a repeating domain structure, alternating between hydrophobic and crosslinking regions.…”
Section: Biomimetic Mechanical Propertiesmentioning
confidence: 99%
“…We, and others, have shown that elastin-like polypeptides (ELPs) derived from the native sequence of elastin act as suitable proxies to study phase separation and elasticity (18,28,31,39). In the present study, we highlight the design and characterization of an elastin mimetic that undergoes phase separation and can be cross-linked to create resilient biomaterials whose assembly can be monitored by NMR to obtain site-specific resolution of structure and dynamics of both the phase-separated and cross-linked materials.…”
Section: Significancementioning
confidence: 99%
“…Conversely, simple coacervation is considered an entropically driven process that depends entirely on hydrophobic interactions between protein chains (4, 16), although few molecular details of this process have been reported. Thus, a detailed understanding of protein structure and dynamics during LLPS is needed to better define the principles governing protein phase separation and to further develop applications of this type of self-assembly in biomaterial design.The elastin monomer, tropoelastin, undergoes a wellcharacterized lower critical solution temperature (LCST) phase transition that is promoted by the presence of salt and heat (8,17,18). Tropoelastin is an IDP consisting of an alternating arrangement of hydrophobic domains (HDs) and cross-linking domains (CLDs) (7,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Current elastin preservative strategies aim to (a) protect existing elastin against degradation by matrix metalloproteinases (MMP) [6] and elastases [7], (b) replace lost elastin structures (e.g., with synthetic elastomers [8,9], peptide-derived elastomers [10,11], allogeneic elastomers [12]), or (c) regenerate elastin matrices by providing appropriate elastogenic cues (e.g., scaffolds, growth factors). However these approaches have thus far met with only limited success due to non-identification of suitable biochemical cues that can upregulate inherently poor tropoelastin synthesis by adult vascular cells.…”
Section: Introductionmentioning
confidence: 99%